Asosiasi Antara Pengumuman Kabinet Baru Tanggai 23 Agustus 2000 Dengan Stock Price Dan Trading Volume Activity Di Pt Bursa Efek Jakarta - Lestari, Sri; Subekti, Imam (TEMA, 2002)
The objective of this study is to find out the correlations between new cabinet declaration on August 23, 2000 and stock exchange reaction, especially Jakarta Stock Exchange (reflected by stock price changes and trading activity). In the next terms, abnormal return proxies the stock price changes. And, trading volume activity (TVA) proxies the trading activity. Event study technique is used for this observation with abnormal return and trading volume activity as dependent variable. Samples will be used in this study is 45 stocks that include in LQ 45 index. Event period that will be analyzed is ten exchange days, and the estimate period is 100 exchange days. The result showed that abnormal return in ten days for the event period is not significant statistically. The test of different mean analy¬sis result about abnormal return before and after that event, showed that both of mean statistically are not significant by different. These were meant that stock price did not have any significant correlation to that event. So, if viewed from abnormal return, there were no reactions of Jakarta Stock Exchange to that event. For stock trans¬action variable that reflected by TVA, the result showed that there were significant differences between TVA mean before and after that event. These showed that stock transaction in Jakarta Stock Exchange had significant correlation with declaration of new cabi¬net on August 23, 2000. In other terms, market made any reactions to that event if viewed from TVA. Keywords: stock exchange; Jakarta Stock Exchange; event study; abnormal return; trading volume activity